Maternal tobacco consumption during pregnancy and risk of congenital heart diseases in offspring - Dev, Deveshwar; Sharma, Rambabu; Sharma, Meenakshi (International Journal of Contemporary Pediatrics, 2018)
Background: Maternal tobacco consumption (both active and passive) during pregnancy as a risk factor for congenital heart diseases in off-springs has been studied by some workers with a small number of subjects hence requires to be evaluated through a study with a significant size of cohort. The objective of the study was to find out the association between maternal tobacco consumption and the risk of CHDs among their off springs. Methods: This is a hospital based, comparative, cross sectional, observational study. 518 children with CHDs, confirmed by echocardiography were included as cases and 240 children without any obvious congenital anomaly matched for age and sex were taken as controls. The following clinical observations were collected through questionnaires in a predesigned Performa: maternal and paternal tobacco consumption during pregnancy; maternal medical, gestational and obstetric history; and other birth defects. Results: Children from case and control groups were comparable with respect to age and sex at the inclusion in the study. Out of the total 758 study participants, 73 children (14.01%) with CHDs had history of maternal tobacco consumption (active consumption) during pregnancy and 86 children (16.6%) with CHDs had history of paternal smoking habit (P value was highly significant). Conclusions: Tobacco consumption during pregnancy (both active and passive) confer an increased risk of CHDs in their off springs (p value <0.001).